Berbagai Daun Tumbuhan Indonesia yang Dapat Menurunkan Tekanan Darah - Putri Herawati (Program Studi S1 Farmasi, STIKES Senior, Medan, 2023)
High blood pressure or hypertension is the third level of cardiovascular disease after coronary heart disease and kidney failure in Indonesia which causes the most deaths. High hypertension becomes a degenerative disease followed by signs of increased blood pressure. In general, there is an increase in systolic blood pressure> 140 mmHg and diastolic blood pressure> 90 mmHg. Giving chemical drugs at long intervals certainly has side effects for the body, therefore people are looking for other solutions using natural Indonesian plant medicines which are believed to reduce blood pressure. Writing this article uses the literature review method, which is done by searching national literature found on Google Schoolar, which means articles published in the last 9 years from 2015-2023 and are articles in complete form. Based on the research results in this article, it was found that the use of herbal medicines from boiled water from Indonesian plant leaves such as: celery, moringa leaves, soursop leaves, green grass jelly leaves, bay leaves, avocado leaves, and cat whiskers have an effect on reducing blood pressure so that they can be a natural treatment option. for people with high blood pressure, but still have to pay attention to the right dose.